In Cultivating an Attitude of Responsibility Through Thematic Learning - Hidayah Nur Wahid; Ida Rindaningsih (Journal of Islamic and Muhammadiyah Studies, 2023)
This study aims to describe the teacher's role in fostering student responsibility through thematic learning in class III SD Muhammadiyah 2 Sidoarjo. By using qualitative research methods. Data collection methods used in the form of Observation, Interview, Documentation and Documents. Data analysis in this study uses descriptive qualitative techniques through data reduction (Data Reduction), data presentation (Data Display) and drawing conclusions (Conclusion drawing/verification). Test the validity of the data in this study using triangulation techniques. The purpose of the data validity test is data that does not differ between the data obtained by the researcher and the data that actually occurs on the object of research so that the validity that has been presented can be justified. The subjects of this research are students and teachers. The results of the first study, Based on data analysis it was found that (1) the teacher played a role as a motivator, inspiration, evaluator in developing students' responsible attitudes through thematic learning. (2) the obstacles experienced by teachers in developing students' responsible attitudes are internal factors that are brought from birth and external factors in the form of the family environment, school, peers, personal experience, the influence of people who are considered important, the influence of culture and mass media.